Wireless Sensor Networks for Vital Signs Monitoring: Application in a Nursing Home - Yuan-Jen Chang; Chin-Hsing Chen; Li-Feng Lin; Ruo-Ping Han; Wen-Tzeng Huang; Guey-Chuen Lee (International Journal of Distributed Sensor Networks)
This study evaluated the application of a wireless sensor network (WSN) on a web-based vital signs monitoring system to nursing homes in Taiwan. The applicability assessment focused on the timely provision of information, information accuracy, system usability, and system accessibility of healthcare systems using a wireless sensor network. Experiments were performed under Internet-based network conditions to verify the timely information provision, especially for a web-based system, including Ajax technology. The accuracy of the information was verified from statistical analyses of the residents’ daily vital sign measurements. A comparison was performed between having and not having a healthcare monitoring system in nursing homes for system usability, system accessibility, and system efficacy. The results indicate that the successful application of a WSN healthcare monitoring system is feasible for use in nursing homes in Taiwan.